2018
DOI: 10.1242/dev.171090
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulation of Nodal-mediated left-right patterning in zebrafish and mouse

Abstract: Nodal is the major effector of left-right axis development. In mice, Nodal forms heterodimers with Gdf1 and is inhibited by Cerl2/Dand5 at the node, and by Lefty1 in the lateral plate mesoderm (LPM). Studies in zebrafish have suggested some parallels, but also differences, between left-right patterning in mouse and zebrafish. To address these discrepancies, we generated single and double zebrafish mutants for southpaw (spaw, the Nodal ortholog), dand5 and lefty1, and performed biochemical and activity assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…1D). Among these were Nodal inhibitors, Dand5/Coco/Cerl2 and Lefty/Antivin (Bell et al, 2003;Cheng et al, 2000;Marques et al, 2004;Meno et al, 1998;Montague et al, 2018), and Pnhd itself, consistent with the reported ability of Pnhd to form dimers (Yan et al, 2019). A top candidate (32 identified peptides) corresponded to Admp, a BMP family protein that is expressed in the Spemann organizer and involved in dorsoventral patterning (Moos et al, 1995;Reversade and De Robertis, 2005).…”
Section: Resultsmentioning
confidence: 79%
“…1D). Among these were Nodal inhibitors, Dand5/Coco/Cerl2 and Lefty/Antivin (Bell et al, 2003;Cheng et al, 2000;Marques et al, 2004;Meno et al, 1998;Montague et al, 2018), and Pnhd itself, consistent with the reported ability of Pnhd to form dimers (Yan et al, 2019). A top candidate (32 identified peptides) corresponded to Admp, a BMP family protein that is expressed in the Spemann organizer and involved in dorsoventral patterning (Moos et al, 1995;Reversade and De Robertis, 2005).…”
Section: Resultsmentioning
confidence: 79%
“…Bilaterally symmetric animals generally show superficial symmetry of external structures but distinct asymmetries in many internal organs. During vertebrate development visceral organs such as the heart and gut tubes bend asymmetrically and develop at predetermined positions favoring the left or right side of the midline [1][2][3][4].…”
Section: Resultsmentioning
confidence: 99%
“…
Vertebrates show conserved left-right (L-R) asymmetry of internal organs controlled by Nodal-Pitx2/Lefty signaling [1][2][3]. Modifications in L-R asymmetry occur in mutants [4] and rarely in humans [5], but little is known about natural L-R changes during evolution. Here we describe changes in L-R asymmetry in Astyanax mexicanus, a teleost with ancestral surface (surface fish) and derived cave (cavefish) morphs [6].
…”
mentioning
confidence: 99%
“…The TGF-beta signals Nodal and Vg1 (Dvr1/Gdf3) play crucial roles in vertebrate development (Schier 2009; Rogers and Muller 2019), including the induction of mesendoderm and the generation of left-right asymmetry (Dale, Matthews, and Colman 1993; Thomsen and Melton 1993; Zhou et al 1993; Conlon et al 1994; Feldman et al 1998; Birsoy et al 2006; Bisgrove, Su, and Yost 2017; Montague and Schier 2017; Pelliccia, Jindal, and Burdine 2017; Levin et al 1995; Collignon, Varlet, and Robertson 1996; Lowe et al 1996; Pagan-Westphal and Tabin 1998; Long, Ahmad, and Rebagliati 2003; Montague, Gagnon, and Schier 2018). For example in zebrafish, secreted Vg1-Nodal heterodimers induce a gradient of signaling that patterns the embryonic mesendoderm (Montague and Schier 2017).…”
Section: Introductionmentioning
confidence: 99%